CLASSIFICATION OF STRUCTURALLY WEAK RURAL REGIONS: APPLICATION OF A RURAL DEVELOPMENT INDEX FOR AUSTRIA AND PORTUGAL - Hennebry, Barraí; Stryjakiewicz, Tadeusz (Quaestiones Geographicae, 2020)
This paper aims to analyse to what extent the level and dynamics of development of rural regions located in two firmly different countries, Austria and Portugal, differ. In order to do this, an index to measure the ‘structural strength’ of rural regions was created. This index is a more holistic measure of socio-economic development than the traditional GDP per capita. After the identification of structurally weak regions in both Austria and Portugal, the paper compares them in the context of challenges faced by such regions.